PENGARUH SUBSTITUSI A. microphylla TERHADAP BOBOT KARKAS, PERSENTASE LEMAK ABDOMEN, BOBOT GIZZARD DAN PANJANG USUS BROILER - Wilda Rahma; Rudy Sutrisna; Purnama Edy Santosa; Farida Fathul (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
This study aimed to determine the best percentage of A. microphylla flour on carcass weight, abdominal fat percentage, gizzard weight and intestine length of broiler. This research was conducted in March--April 2021 at PT. Sinar Ternak Sejahtera farm 5 in Wonodadi Village, South Lampung Regency, Lampung Province. Carcass processing was carried out at the Livestock Production Laboratory in the Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The experimental design used was a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments were basal ration (P0), basal ration with substitution of A. microphylla 2.5% (P1), basal ration with substitution of 5% A. micophylla (P2), and basal ration with substitution of A. microphylla 7.5% (P3). The data obtained were analyzed using analysis of variance with a significance level of 5% and continued with Duncan's Multiple Range test. The results showed that the substitution of A. microphylla on carcass weight and percentage of abdominal fat had a significant effect (P<0.05) and had no significant effect (P>0.05) on gizzard weight and intestine length of broiler. Keywords: A. microphylla, Carcass weight, Abdominal fat percentage, Gizzard weight, Intestinal length